Enhanced Analysis and Development of Technical Features, Performance, and Occupational Safety in Syringe Needle Destroyers for Advancing Medical Standards - Pansrinual, Weeraphol; Thongsin, Orraya; Vanpetch, Wichai; Muangmongkun, Tanaporn; Chailikit, Orajit; Chanmuang, Napaphach; Sarikha, Sasinpakorn; Saetiaw, Paemika; Anumanee, Adcharasiri; Siripan, Apisan; Phumee, Wilawan; Yamada, Kou; et al. (วารสารวิศวกรรมศาสตร์และเทคโนโลยีอุตสาหกรรมบ้านสมเด็จ, 2026)
This paper aims to evaluate the overall suitability of syringe needle destruction devices (SNDDs) in healthcare environments by analyzing how technical attributes, operational performance, and safety/usability influence user acceptance. While SNDDs are widely implemented to reduce needlestick injuries (NSIs) and improve waste management, critical design issues such as overheating, inefficient needle insertion, and limited ergonomic safety remain inadequately addressed. A structured 5-point Likert scale questionnaire was administered to 400 healthcare professionals in Bangkok, including nurses, physicians, medical technologists, and sanitation staff, each with a minimum of six months of device experience. The assessment focused on three key dimensions: technical quality (e.g., destruction reliability, structural design, electrical safety), performance (e.g., destruction speed, consistency), and usability/safety (e.g., ergonomics, heat exposure, ease of operation). Multiple linear regression revealed that technical attributes were the most significant positive predictor of overall suitability (β₁ = 0.1450, p < 0.0001), while operational performance (β₂ = –0.0251, p = 0.0797) and safety/usability (β₃ = –0.0113, p = 0.4186) had negligible or slightly negative effects. The regression model exhibited strong explanatory power (R² ≈ 0.66), and residual analysis confirmed its statistical adequacy. These results highlight the central role of robust technical engineering in shaping user satisfaction and acceptance, emphasizing that structural integrity, mechanical reliability, and conformity to ISO/IEC safety standards outweigh incremental gains in operational speed or superficially integrated safety features. The findings demonstrate that high-quality technical design directly supports clinical usability, operational safety, and confidence in daily device deployment.